Sales Taxes and Internet Commerce - Einav, Liran; Knoepfle, Dan; Levin, Jonathan; Sundaresan, Neel (American Economic Review, 2014)
We estimate the sensitivity of Internet retail purchasing to sales taxes using eBay data. Our first approach exploits the fact that a seller's location—and therefore the applicable tax rate—is revealed only after a buyer has expressed interest in an item. We document how adverse tax “surprises” reduce the likelihood of purchase and shift subsequent purchases toward out-of-state sellers. We then use more aggregated data to estimate that every one percentage point increase in a state's sales tax increases online purchases by state residents by almost 2 percent, while decreasing their online purchases from state retailers by 3–4 percent. (JEL H71, L81, L86)